ANALISIS KEBUTUHAN BUKU WORDLESS PICTURE BOOK UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF DALAM PEMBELAJARAN PENDIDIKAN PANCASILA PADA SISWA KELAS 5 SD - Nina Nurhasanah; Iva Sarifah; Uswatun Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The development of creative thinking in learning Pancasila education is still not optimal due to the limited availability of books in schools. The books used are student books which still do not provide enough stimulus for students to think creatively. This research aims to develop Wordless Picture Book teaching materials to improve the creative thinking abilities of 5th-grade students at the UNJ PGSD Laboratory Elementary School. The research uses the Rn D method based on the initial stages of the ADDIE model, namely Analysis by Borg and Gall. The instrument used is a questionnaire sheet with descriptive quantitative data type. The research data results show that there is not enough open material in storybooks to improve creative thinking skills. Students and teachers need interesting and challenging storybooks to develop creative thinking skills. One alternative open material is a wordless picture book.